Students’ English Writing Process and Problems: A Case Study at Hamzanwadi University - Maysuroh, Siti; Maryadi, Lalu Ilham; ., Supiani (VELES Voices of English Language Education Society, 2017)
Writing is a very crucial skill in teaching and learning English as a Foreign Language (EFL). However, many students especially in Indonesia regarded this skill as the most complex task to complete, even for university students. Thus, the aim of this study was to describe the process of teaching writing in the classroom as well as to identify the students’ writing problems and to find out the factors which cause them. The study was conducted in the second semester of English language program of Hamzanwadi University in academic year 2016-2017. The participants of this study consisted of 10 students selected using purposesful sampling technique. The research method used was a case study approach. In addition, in order to collect the data in the field, the researcher used some instruments; observation, interview, document and records. In addition, to ensure the trustworhiness of the data, the researcher followed some criteria adapted by Lincoln and Guba (1985), namely credibility (truth), dependability (consistency), transferability (applicability), and confirmability (Neutrality). The findings reveal that the students were taught using process approach in which the students were encouraged to learn writing throught some processes namely pre-writing, drafting, revising, editing, and publishing. The researcher found that the students have various problems in their writing; mostly grammatical problems, word choice problems, and mechanical problems. They might be caused by some factors; lack practice, low motivation, and also time allocation.